PRIME HOLLOW MODULES - Ahmed, Muna (Iraqi Journal of Science, 2024)
A non-zero module M is called hollow, if every proper submodule of M is small.In this work we introduce a generalization of this type of modules; we call it primehollow modules. Some main properties of this kind of modules are investigated andthe relation between these modules with hollow modules and some other modulesare studied, such as semihollow, amply supplemented and lifting modules.